1996
DOI: 10.1093/oxfordjournals.aje.a008690
|View full text |Cite
|
Sign up to set email alerts
|

Falls in the Elderly: A Prospective Study of Risk Factors and Risk Profiles

Abstract: In this prospective study, the authors determined intrinsic risk factors for falls and recurrent falls and constructed a risk profile that indicated the relative contribution of each risk factor and also estimated the probabilities of falls and recurrent falls. In 1992, over a 28-week period, falls were recorded among 354 elderly subjects aged 70 years or over who were living in homes or apartments for the elderly in Amsterdam and the vicinity. During the study period, 251 falls were reported by 126 subjects (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
429
2
49

Year Published

2003
2003
2014
2014

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 670 publications
(501 citation statements)
references
References 28 publications
13
429
2
49
Order By: Relevance
“…In most cases, multiple risk factors for falls exist, such as age 17 , a history of past falls 18,19 , and medical diagnoses such as cardiac conditions 20 . Factors relating to gait and balance are also important 19,21 , as are visual limitations 22 and cognitive impairment 23 . ; yet, in a busy practice, it may be difficult to identify strategies to impact this problem.…”
Section: Discussionmentioning
confidence: 99%
“…In most cases, multiple risk factors for falls exist, such as age 17 , a history of past falls 18,19 , and medical diagnoses such as cardiac conditions 20 . Factors relating to gait and balance are also important 19,21 , as are visual limitations 22 and cognitive impairment 23 . ; yet, in a busy practice, it may be difficult to identify strategies to impact this problem.…”
Section: Discussionmentioning
confidence: 99%
“…Both polyarthritis (29) and dizziness (17,30) are well-documented risk factors for falls among elderly persons. In a review of the epidemiology of falls, dizziness was reported as the cause of a fall in 13% of 3,628 reported falls among both community-dwelling and institutionalized elderly (17).…”
Section: Discussionmentioning
confidence: 99%
“…The predictors of falls were based on a previous study carried out in homes for the elderly in The Netherlands [26] and on the literature [6,16,17]. Potential predictors were classified into nine categories: socio-demographic characteristics, chronic diseases and drug use, physical impairments and general health, body composition, physical activity and mobility, psychosocial functioning, life style factors, biochemical markers and other potentially fall-related predictors.…”
Section: Predictorsmentioning
confidence: 99%